Efficacy of Oral Itraconazole in the Treatment of Seborrheic Dermatitis (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: Seborrheic dermatitis is a common papulosquamous  dermatosis and occurring in 2% to 5% of the  population. The prevalence of seborrheic dermatitis among  HIV-positive and AIDS patients between 34% and 83%. The  anti-inflammatory activity of oral itraconazole and efficacy  on Malessezia suggests that itraconazole capsule will be the  first oral treatment option in future in seborrheic dermatitis.  Unfortunately there is no data base study with the efficacy  of oral itraconazole for the treatment of seborrheic  dermatitis over Bangladeshi people.Objectives: To evaluate the efficacy of itraconazole in the  treatment of Seborrheic dermatitis.Methods: This was an interventional type of study and total  thirty seven patients of seborrheic dermatitis from department  of Dermatology and Venereology, Bangabandhu Sheikh  Mujib Medical University (BSMMU) was enrolled. The study  was carried out for a period of two years from January 2008  to December 2009 and purposive type non-probability  sampling technique was followed in this study.Results: The scoring of seborrhea was 6.33±1.15 before  treatment and 4.33 ±3.21 after treatment, scoring of itching  was 6.66 ±1.49 before treatment and 3.61 ±2.70 after  treatment and scoring of greasy crust was 7.12 ±2.70 before  treatment and 4.00 ±3.16 after treatment. It was observed  that before treatment, erythema was severe in 43.2% cases,  moderate in 51.4% cases and mild type erythema was present  in 5.4% cases. And after treatment, 29.7% had severe type  erythema, no patient had moderate type erythema, only  43.2% had mild type and 27% cases had no erythema at all.  Before treatment, papular eruption was severe in 27% cases,  moderate in 54.1% cases and only 18.9% had mild type  papular eruption. But after treatment, 10.8% had severe  type, 18.9% had moderate, 51.4% had mild and 18.9% had  no papular eruption at all. It was observed that before  treatment, squamation was severe in 37.8% cases and  moderate in 62.2% cases. But after treatment, 18.9% had severe type squamation, 10.8% had moderate, 45.9% had  mild and 24.3% had no squamation. Improvement was  shown in 26(70.27%) cases and 11(29.73%) cases shown  no improvement at all.Conclusion: The study suggests that oral itraconazole has significant efficacy profile for treatment option of seborrheic dermatitis. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11326 J Bangladesh Coll Phys Surg 2011; 29: 201-206